Chemical engineering science (Pergamon Press, 1951)
"The journal publishes papers on the fundamentals of chemical engineering, including applications of the basic sciences. Descriptions of original experiments are acceptable and likewise developments in theory; papers combining new experiments with theoretical insight are especially welcome. The range of industrial activity which defines issues suitable for the journal is interpreted broadly, including oil, chemicals, pharmaceuticals, food and new materials."
Keywords: Chemical engineering : Periodicals